The M. tuberculosis Phosphate-Binding Lipoproteins PstS1 and PstS3 Induce Th1 and Th17 Responses That Are Not Associated with Protection against M. tuberculosis Infection. (7th March 2011) - Palma, Carla; Spallek, Ralf; Piccaro, Giovanni; Pardini, Manuela; Jonas, Fatima; Oehlmann, Wulf; Singh, Mahavir; Cassone, Antonio
Abstract : The M. tuberculosis phosphate-binding transporter lipoproteins PstS1 and PstS3 were good immunogens inducing CD8 + T-cell activation and both Th1 and Th17 immunity in mice. However, this antigen-specific immunity, even when amplified by administration of the protein with the adjuvant LTK63 or by the DNA priming/protein boosting regimen, was not able to contain M. tuberculosis replication in the lungs of infected mice. The lack of protection might be ascribed with the scarce/absent capacity of PstS1/PstS3 antigens to modulate the IFN- γ response elicited by M. tuberculosis infection during which, however, PstS1-specific IL-17 secreting cells were generated in both unvaccinated and BCG-vaccinated mice. In spite of a lack of protection by PstS1/PstS3 immunizations, our results do show that PstS1 is able to induce IL-17 response upon M. tuberculosis infection which is of interest in the study of anti- M. tuberculosis immunity and as potential immunomodulator in combined vaccines.